THE RELATIONSHIP BETWEEN TEACHERS’ ORGANIZATIONAL COMMITMENT, EFFECTIVE TEACHING PRACTICES, AND STUDENTS’ LEARNING OUTCOMES IN THE SECONDARY SCHOOLS, PAKISTAN - Niaz Ali; Majid Mohd Isa; Abdul Rahman S Senathirajah; Muhammad Adnan; Muhammad Niqab; Shakil Ahmad; Ian Phil Canlas (PUPIL: International Journal of Teaching, Education and Learning, 2025)
Teacher commitment and instructional quality are established predictive factors of student achievement; however, empirical investigations of their interplay within resource-constrained environments, such as Pakistan, remain sparse. This research explores the interplay of teachers’ organizational commitment, effective pedagogical practices, and instructional outcomes within secondary schools in Khyber Pakhtunkhwa. Employing a quantitative survey framework, data was collected from a purposive sample of 320 teachers. A previously validated instrument operationalized three latent constructs: organizational commitment (affective, normative, continuance), effective teaching practices (clarity, metacognitive strategies, feedback, formative assessment), and student outcomes (cognitive and non-cognitive dimensions). Descriptive statistics, correlation analysis, and structural equation modeling were used to evaluate the data. The analysis revealed moderate indices of teacher commitment and teaching effectiveness, juxtaposed against low student outcomes, especially in non-cognitive areas. Positive and statistically significant correlations appeared between commitment and practices, and between practices and outcomes. The mediational analysis revealed that teaching practices wholly mediated the linkage between commitment and outcomes, rendering the direct effect of commitment on outcomes statistically non-significant. These findings underscore the mediating influence of pedagogical practices in converting teacher commitment into measurable student success. Within resource-limited contexts, strategic investment in commitment—via professional recognition, structured mentoring, and participatory leadership—coupled with continuous pedagogical training, is recommended to amplify student engagement and achievement.